Outcome of Surgical Treatment of Degenerative Lumbar Spinal Stenosis. - Thapa, Bishnu Babu; Magar, Sushil Rana; Chand, Pankaj; KC, Bachhu Ram (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Spinal stenosis mostly occur in lumbar spine and causes back pain, leg pain & neurogenic claudication. Although conservative treatment is mainstay, decompression with or without fusion (with or without instrumentation) can be considered in non-responsive cases. However, long term outcome of the surgery is controversial. The aim of our study was to analyze the outcome of surgery in lumbar spinal stenosis in terms of post-operative pain and claudication distance. Methods: A prospective analysis of patients who underwent decompression or decompression with fusion (with or without instrumentation), after failure of 3-6 months conservative treatment, for lumbar spinal stenosis were conducted. Only those who were operated and followed up for at least two years were included.Their preop and postop VAS score and walking distance compared. Results: Of 22 cases enrolled in this study, VAS score was improved in 21 patients and walking distance increased. Only one patient complained of increase in pain score at 24 months. Conclusion: Operative management is a good option for selected patients, 21 out of 22 have improved VAS and claudication distance in our study